Circular RNA 0039411 Is Involved in Neodymium Oxide-induced Inflammation and Antiproliferation in a Human Bronchial Epithelial Cell Line via Sponging miR-93-5p. (23rd March 2019) - Hua, Qiuhan; Chen, Yingnan; Liu, Yufei; Li, Meizhen; Diao, Qinqin; Xue, Hainan; Zeng, Huixian; Huang, Lihua; Jiang, Yiguo
Abstract: Adverse health effects induced by neodymium oxide (Nd2 O3 ) particles have raised concern as a result of their increasing applications in various arenas. However, information on their potential cytotoxicity is currently limited. In the present study, we investigated the underlying cytotoxicity of Nd2 O3 in human bronchial epithelial cells (16HBE) and the potential mechanisms mediated by circular RNAs (circRNAs). Nd2 O3 exposure initiated an inflammatory response in 16HBE cells via the release of the proinflammatory cytokines interleukin (IL)-6 and IL-8. The 5-ethynyl-2′-deoxyuridine assays showed that Nd2 O3 treatment inhibited 16HBE cell proliferation and caused cell cycle arrest at G0/G1 phase and cell apoptosis. Microarray analyses demonstrated that Nd2 O3 treatment altered circRNA expression profiles and significantly upregulated circRNA 0039411 (circ_0039411) in 16HBE cells. Further functional studies showed that silencing circ_0039411 prevented Nd2 O3 -induced inflammation and reversed its antiproliferative effect by moderating the G0/G1 phase cell cycle arrest, whereas overexpression of circ_0039411 had the opposite effects. Luciferase reporter assays showed that circ_0039411 bound to miR-93-5p, whereas fluorescence in situ hybridization showed that circ_0039411 and miR-93-5p colocalized in the cytoplasm. Moreover, transfection of 16HBE cells with a miR-93-5p mimic decreased the phosphorylation of signal transducer and activator of transcription 3 (STAT3). The levels of phospho-STAT3 were decreased by circ_0039411 silencing and elevated after circ_0039411 overexpression. These results suggested that upregulation of circ_0039411 mediated Nd2 O3 -induced inflammation and dysfunction by sponging miR-93-5p.